2021
DOI: 10.1002/clc.23600
|View full text |Cite
|
Sign up to set email alerts
|

Low‐density lipoprotein cholesterol lowering in real‐world patients treated with evolocumab

Abstract: Background Low‐density lipoprotein cholesterol (LDL‐C) is a risk factor for atherosclerotic cardiovascular disease (ASCVD). There are limited real‐world data on LDL‐C lowering with evolocumab in United States clinical practice. Hypothesis We assessed LDL‐C lowering during 1 year of evolocumab therapy. Methods This retrospective cohort study used linked laboratory (Prognos) and medical claims (IQVIA Dx/LRx and PharMetrics Plus®) data. Patients with a first fill for evolocumab between 7/1/2015 and 10/31/2019 (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
1
0
1
Order By: Relevance
“…Although up to a 70% reduction in LDL-C was reported in Phase III clinical trials, 25 and an expected up to 85% in triple LLT combination as stated in the ESC/EAS guidelines, 5 other real-world experience studies performed following regulatory approval of evolocumab reported LDL-C reductions averaging from 40% to 60%, [27][28][29][30][31][32][33] which is comparable to our findings. LDL-C reductions of 39%, 52.3%, 54.9%, and 60% were observed in PCSK9 treatment groups in reports by Sarsam et al, 26 Koren et al, 27 Santos et al, 28 and Desai et al 29 In the present study, introduction pf evolocumab helped attain the ACC/AHA guidelines-recommended reduction in LDL-C ( ≥30% reduction or LDL-C < 2.6 mmol/L in primary prevention or ≥50% reduction or LDL-C < 1.8 mmol/L in secondary prevention) not only as add-on therapy to statins but also as a combination with other LLTs in statin-intolerant patients. Voutyritsa et al 34 reported greater (up to 70%) reductions in LDL-C with evolocumab when administered with other LLTs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although up to a 70% reduction in LDL-C was reported in Phase III clinical trials, 25 and an expected up to 85% in triple LLT combination as stated in the ESC/EAS guidelines, 5 other real-world experience studies performed following regulatory approval of evolocumab reported LDL-C reductions averaging from 40% to 60%, [27][28][29][30][31][32][33] which is comparable to our findings. LDL-C reductions of 39%, 52.3%, 54.9%, and 60% were observed in PCSK9 treatment groups in reports by Sarsam et al, 26 Koren et al, 27 Santos et al, 28 and Desai et al 29 In the present study, introduction pf evolocumab helped attain the ACC/AHA guidelines-recommended reduction in LDL-C ( ≥30% reduction or LDL-C < 2.6 mmol/L in primary prevention or ≥50% reduction or LDL-C < 1.8 mmol/L in secondary prevention) not only as add-on therapy to statins but also as a combination with other LLTs in statin-intolerant patients. Voutyritsa et al 34 reported greater (up to 70%) reductions in LDL-C with evolocumab when administered with other LLTs.…”
Section: Discussionsupporting
confidence: 89%
“…Voutyritsa et al 34 reported greater (up to 70%) reductions in LDL-C with evolocumab when administered with other LLTs. Desai et al 29 observed an LDL-C reduction of up to 60% in a real-world setting. Gürgöze et al 17 reported that the addition of evolocumab to other LLTs lowered LDL-C levels by ∼60%.…”
Section: Discussionmentioning
confidence: 96%
“…In the newly treated PCSK9i receivers, we assume that the PCSK9i LDL-C lowering is not yet fully effective at enrolment due to a short period between laboratory measurement and patient enrolment. This result is in line with other reports but varied in comparison to the data from Switzerland (75% of patients < 70 mg/dl) [ 24 ] and data from Phar Metrics observations (62.1–69.7% < 70 mg/dl) [ 25 ]. Importantly, our study shows that PCSK9i are preferentially used in patients with considerably higher baseline LDL-C compared to the clinical development studies.…”
Section: Discussionsupporting
confidence: 91%
“…Desai и соавт. [8], где на амбулаторном этапе исследования до усиления терапии эвалокумабом прием гиполипидемической терапии зарегистрирован лишь у 70,7% больных. В исследовании ALIGN среди пациентов, перенесших инфаркт миокарда, при первичном обращении только 27 из 33 (81,8%) получали или ингибиторы ангиотензинпревращающего фермента (ИАПФ) или блокаторы рецепторов ангиотензина II (БРА), а бета-адреноблокаторы (ББ) -29 из 33 (87,9%) больных.…”
Section: Introductionunclassified